LEGAL ASPECTS OF MEDICAL PRACTICE IMPLEMENTATION: DISPUTES OF CODE OF ETHICS IN HANDLING PATIENTS HEALTH SOCIAL SECURITY ADMINISTERING AGENCY - Nabbilah Amir; Anissa Rachma Damayanti (Center for Constitutional and Legislative Studies University of Bandar Lampung, 2022)
The Health Social Security Administering Body is a public legal entity whose main task is to provide improved health services to the entire community. With the existence of health insurance products, it is hoped that all Indonesian people can experience health services equally to all levels of society. Doctors are one of the leading professions in the health sector. The main task of a doctor is to provide optimal service to everyone who has problems with their health interests in accordance with and carried out in accordance with the doctor’s professional code of ethics. This research is juridical normative, which is a form of research that will analyze a problem and solve it using legal materials obtained based on facts, literature, and expert arguments and analyze article by article in the legislation so that the results of this study will provide a explanation of existing legal issues to be used as guidelines in improving medical service standards by the government. There are quite a lot of participants in the Health Social Security Organizing Agency in Indonesia. This shows that more and more people need easy access to health services. This must be supported by human resources (doctors, nurses, and related parties) and agencies such as hospitals or health centers in improving the quality of health services. A doctor has a professional code of ethics in carrying out his duties, namely he must carry out health services seriously in accordance with his competence to be able to provide optimal service to patients while respecting human dignity.